BrainQuake: An Open-Source Python Toolbox for the Stereoelectroencephalography Spatiotemporal Analysis - Cai, Fang; Wang, Kang; Zhao, Tong; Wang, Haixiang; Zhou, Wenjing; Hong, Bo (Frontiers in Neuroinformatics, 2022)
Intracranial stereo-electroencephalography (SEEG) is broadly used in pre-surgical evaluation of intractable epilepsy, due to its high temporal resolution in neural activity recording and high spatial resolution within suspected epileptogenic zones. Neurosurgeons or technicians face the challenge of conducting a workflow of post-processing operations with multi-modal data (e.g. MRI, CT, EEG) after an implantation surgery, including brain surface reconstruction, electrode contact localization, and SEEG data analysis. Several software or toolboxes have been developed to take one or more steps in the workflow but without an end-to-end solution. In this article, we introduce BrainQuake, an open-source Python software for SEEE spatiotemporal analysis, integrating modules and pipelines in surface reconstruction, electrode localization, seizure onset zone (SOZ) prediction based on ictal and inter-ictal SEEG analysis, and final visualizations, each of which is highly automated with a user-friendly graphical user interface (GUI). BrainQuake also supports remote communications with a public server, which is facilitated with automated and standardized preprocessing pipelines, high-performance computing power, and data curation management to provide a time-saving and compatible platform for neurosurgeons and researchers.